Determinants of the Quality of Buildings by Contractors Within Mavoko Municipality - Busolo, Victor; Ombuki, Charles (My University, 2014)
Construction industry is big in terms of its contribution to the economy; its performance affects the performance of the economy. Knowing the factors that affect the performance of the industry deserves undivided attention. Building contractors are one of the key players in the industry and their performance too is important. This study sought to investigate the factors affecting the performance of the building contractors especially in Mavoko Municipality. The objectives of the study were to determine the effect of quality of workmanship on performance of building contractors, to investigate the extent to which statutory requirements affect the performance of building contractors, to examine the effect of project management capabilities on the performance of building contractors and to establish the extent to which government supervision has affected the performance of building contractors. The study adopted a descriptive research design using purposive sampling method to come up with a sample size of 50 respondents. The target population for the study was the building contractors in Mavoko Municipality and its environs and the clients involved in Mavoko Municipality building construction. Out of the target population, 32 employees were targeted from the construction companies together with 18 clients making total sample size to be 50. Purposive sampling was used to attain this sample size. The instrument for collecting data was the questionnaire. The data collected was analyzed using descriptive statistics using measures of central tendencies.